2014
DOI: 10.1371/journal.pone.0095125
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation-Linked Germline GJA5/Connexin40 Mutants Showed an Increased Hemichannel Function

Abstract: Mutations in GJA5 encoding the gap junction protein connexin40 (Cx40) have been linked to lone atrial fibrillation. Some of these mutants result in impaired gap junction function due to either abnormal connexin localization or impaired gap junction channels, which may play a role in promoting atrial fibrillation. However, the effects of the atrial fibrillation-linked Cx40 mutants on hemichannel function have not been studied. Here we investigated two atrial fibrillation-linked germline Cx40 mutants, V85I and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…In contrast, the expression of V85I, L221I or L229M in N2A cell pairs did not show any reduction of the G j , indicating an apparently normal GJ coupling of these mutants. Further investigations revealed that L229M, but not V85I and L221I, displayed a transdominant negative action on the G j of co‐expressed Cx43 [100,102]. These studies indicate that many of the AF‐linked Cx40 mutants showed impairment of GJ channels via different mechanisms (Table 1 ), which may play a role in promoting atrial arrhythmias leading to AF.…”
Section: Atrial Fibrillation‐linked Connexin Mutations and Mutant/knomentioning
confidence: 88%
See 3 more Smart Citations
“…In contrast, the expression of V85I, L221I or L229M in N2A cell pairs did not show any reduction of the G j , indicating an apparently normal GJ coupling of these mutants. Further investigations revealed that L229M, but not V85I and L221I, displayed a transdominant negative action on the G j of co‐expressed Cx43 [100,102]. These studies indicate that many of the AF‐linked Cx40 mutants showed impairment of GJ channels via different mechanisms (Table 1 ), which may play a role in promoting atrial arrhythmias leading to AF.…”
Section: Atrial Fibrillation‐linked Connexin Mutations and Mutant/knomentioning
confidence: 88%
“…Interestingly that Q49X also reduced the localization of wild‐type Cx40 and Cx43 to the cell–cell interfaces and their G j [101]. In contrast to Q49X, all other AF‐linked germline mutants (I75F, V85I, A96S, L221I and L229M) did not show any major defects in the localization and formation of GJ plaques at the cell–cell interfaces [96,100,102]. However, dual patch clamp studies indicated that both I75F and A96S virtually eliminated G j in cell pairs expressing these mutants [96,100].…”
Section: Atrial Fibrillation‐linked Connexin Mutations and Mutant/knomentioning
confidence: 99%
See 2 more Smart Citations
“…Several SNPs of the gene encoding Cx40 lead to abnormal connexin localization and impaired gap junction channels (Sun et al, 2014). This aberration may result in the development of AF.…”
Section: Introductionmentioning
confidence: 99%